1992
DOI: 10.1083/jcb.117.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta 1 in the rat brain: increase after injury and inhibition of astrocyte proliferation

Abstract: Abstract. Transforming growth factor-ßl (TGF-ßl) has been shown to up-regulate the synthesis of nerve growth factor (NGF) in cultured rat astrocytes and in neonatal brain in vivo (Lindholm, D., B. Hengerer, R Zafra, and H. . NeuroReport. 1:9-12) . Here we show that mRNA encoding TGF-01 increased in rat cerebral cortex after a penetrating brain injury. The level of NGF mRNA is also transiently increased after the brain trauma, whereas that of brain-derived neurotrophic factor remained unchanged. In situ hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
251
1
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 467 publications
(272 citation statements)
references
References 51 publications
17
251
1
3
Order By: Relevance
“…10 TGF-p1 (ng/ml) ronal injury and neuronal plasticity. Based on a study in which a model of penetrating brain injury in the rat was used (Lindholm et al, 1992), and also on a postmortem study of brains of patients with ac quired immune deficiency syndrome (Wahl et al, 1991), it has been suggested that TGF-�l may derive from penetrating macrophages or activated microg lia. In cultured rat astrocytes, TGF-�l is produced and released upon stimulation with the cytokine in terleukin-1 (da Cunha and Vitkovic, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…10 TGF-p1 (ng/ml) ronal injury and neuronal plasticity. Based on a study in which a model of penetrating brain injury in the rat was used (Lindholm et al, 1992), and also on a postmortem study of brains of patients with ac quired immune deficiency syndrome (Wahl et al, 1991), it has been suggested that TGF-�l may derive from penetrating macrophages or activated microg lia. In cultured rat astrocytes, TGF-�l is produced and released upon stimulation with the cytokine in terleukin-1 (da Cunha and Vitkovic, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…18 These cells can produce substantial amounts of trophic factors that protect neurons affected by the lesions. In addition, astrocytes provide a 'natural' site where several growth factors including GDNF [35][36][37][38] are synthesized in specific areas and time points. Thus, astrocytes provide a most efficient target to express trophic factors in neurodegenerative diseases such as PD.…”
Section: Discussionmentioning
confidence: 99%
“…An important physiologic role of TGF-b within the brain appears to be termination of the glial proliferative response to injury and/or cytokine-induced stimulation (Lindholm et al, 1992;da Cunha et al, 1993). Among quiescent newborn rat cerebral glia, serum induction of DNA synthesis is delayed and attenuated by TGF-b1.…”
Section: Role Of Tgf-b As a Negative Regulatory Cytokine In Glioblastomamentioning
confidence: 99%